Optimization and field application of reservoir stimulation of the Sinian Deng 4 member in the Sichuan Basin - Lang Zhou (Natural Gas Industry B, 2022)
The main zone of production of Sinian gas reservoirs in the Sichuan Basin (China) is the Deng 4 member of the Gaoshiti–Moxi structure. In the Deng 4 member, the rock type is mostly dolomite, and the main types of storage space are brecciated interporosity and large-scale interporosity characterized by low porosity and low permeability (average porosity: 3.21%, average permeability: 2.19 mD). In the Gaoshiti structure of the Deng 4 member gas reservoir, annual gas production of 60 billion cubic meters has been realized using differential segmented acid fracturing stimulation technology. However, with development of the Moxi structure, such technology is unable to adapt the reservoir because it requires continuous optimization according to reservoir characteristics. To provide effective support for optimization of reservoir stimulation technology, this study performed experiments using a large-scale true triaxialacid fracturing model. On the basis of the simulation of the reservoir reconstruction process, optimization of the process was investigated, an optimization scheme was proposed, and a field test was performed. The results, which indicated that gelling acid fracturing technology can effectively improve the stimulation effect of the Deng 4 member of the Moxi gas reservoir and substantially increase single-well production, could provide technical support for enhanced production of the Gaoshiti–Moxi gas reservoir.